Real-world safety of ulinastatin: a post-marketing surveillance of 11,252 patients in China - Jin Li; Meijun Li; Liren Li; Lin Ma; Ailin Cao; Aiping Wen; Wenge Chen; Lingling Li; Yan Liang; Jianxiong Deng (BMC, 2022)
Abstract Background The safety assessment of ulinastatin can guide clinical practice. The present study aimed to investigate the real-world safety of ulinastatin in China. Methods This multicenter study retrospectively analyzed the post-marketing surveillance data of consecutive patients treated with ulinastatin between August 2014 and June 2017 in the general wards and the intensive care units (ICU) of nine hospitals in China. Adverse drug reactions/adverse drug events (ADRs/ADEs) were collected and evaluated in a post-marketing database. Results A total of 11,252 consecutive patients were included in the study: 7009 ICU patients and 4243 general ward patients. Eleven patients with ADRs/ADEs were observed, including nine ICU patients and two general ward patients. The clinical manifestations were liver dysfunction (n = 5 ICU cases, n = 1 general case), thrombocytopenia (n = 2 ICU cases, n = 1 general case), leukopenia (n = 1 ICU case), and rash (n = 1 ICU case). During the study period, the drug ADR/ADE rate of ulinastatin injection was 0.98‰ (11/11,252 × 1000‰). Among the 11,252 valid patients, only 327 received ulinastatin in accordance with the drug specifications. After excluding unreasonable drug use, the calculated ADR rate was 3.06‰ (1/327 × 1000‰) (95% confidence interval: 0.0‰-17.1‰). In ICU and general ward patients, the use of other drugs combined with ulinastatin was associated with the occurrence of ADRs/ADEs (100% with ADRs/ADEs vs. 0% in controls, P < 0.001). Conclusions The incidence of ADRs/ADEs of ulinastatin is < 5‰. The ADRs/ADEs involved limited organs, mainly the skin, gastrointestinal tract, and blood. In most cases, the ADRs/ADEs gradually alleviated or recovered after drug withdrawal. The inappropriate/off-label use of ulinastatin should be the focus of surveillance.